Triagem neonatal no estado de Mato Grosso : avaliação do Serviço de Referência em Triagem Neonatal (SRTN) e triagem neonatal para galactosemia - Costa, Roseli Divino (2023)
In Brazil, Biological Neonatal Screening began in 1976 in SP, at the Association of Parents and Friends of the Disabled with the testing of phenylketonuria and, from 1980, for the screening of Congenital Hypothyroidism. Galactosemia is an inborn error of metabolism, of autosomal recessive inheritance, caused by the deficiency of one of the enzymes of the Leloir pathway: GALK, GALT and GALE. Screening for galactosemia only occurs in some states in Brazil, and, according to Law No. 14,154, of May 26, 2021, this screening will be implemented in stage 2. The object of the present study is to evaluate the Reference Service in Neonatal Screening of the State of Mato Grosso (NSRS/MT) from 2005 to 2019 and the incidence of galactosemia in the State of Mato Grosso in the year 2019. NT coverage was below the national average and the incidences of diagnosed diseases are compatible with national data. The average age of children at the first consultations was above the national average. In relation to the time between collection and delivery of the sample to the SRTN, release of results and return of those recalled, it was above what was recommended. The number of collection points is below the DATASUS quantity and collection in the ideal period was also below expectations. In the State of Mato Grosso, galactosemia was diagnosed in a proportion of 1 in every 17,079 live births screened. During the study, four different variants in the GALT gene were identified, namely: c.563A>G (p.Gln188Arg), c.226C>T (p.Pro76Ser), c.983G>A (p.Arg328His) and c .855G>T (p.Lys285Asn).